P‐glycoprotein: a role in the export of amyloid‐β in Alzheimer's disease?. (9th December 2019) - Chai, Amanda B.; Leung, Gavin K. F.; Callaghan, Richard; Gelissen, Ingrid C.
Abstract : The accumulation of amyloid‐β (Aβ) peptides is a key histopathological feature of the Alzheimer's brain. Defective clearance mechanisms result in toxic levels of soluble Aβ40 and Aβ42 oligomers, leading to impaired synaptic function, neurodegeneration and cognitive decline. Growing evidence points to the involvement of P‐glycoprotein (P‐gp or ABCB1), an ATP‐binding cassette transporter highly expressed on the luminal side of the blood–brain barrier, in facilitating the clearance of Aβ from the brain. In this review, we summarise evidence from human, animal and in vitro studies examining the contribution of P‐gp to Aβ clearance, and discuss the potential for P‐gp as a novel pharmacological target in Alzheimer's disease (AD). P‐gp expression and activity in the brain are inversely correlated with ageing, Aβ deposition and AD. Moreover, Aβ itself has been found to compromise the expression of P‐gp, thereby exacerbating Aβ deposition and disease. Despite decades of research, the pathophysiology of AD remains elusive. Understanding the normal versus impaired processing and clearance mechanisms affecting Aβ peptides will assist the development of more effective therapeutic agents to combat this progressive neurodegenerative condition that continues to devastate millions of patients globally. Abstract : Defective clearance mechanisms in the Alzheimer's brain lead to the toxic accumulation of amyloid‐β (Aβ) peptides. The multidrug transporter P‐glycoprotein (P‐gp), which regulates the brain environment by exporting compounds across the blood–brain barrier, has also been identified to export Aβ. Here, we discuss the evidence surrounding the contribution of P‐gp to Aβ clearance and Alzheimer's pathophysiology.